The Neonatal Screening for Sickle Cell Disease, Thalassemia, and G6PD Deficiency in Central India - Rakesh K. Jha; Meghali Kaple; Ranjit S. Ambad; Archana Dhok; Ashsish Anjankar (Journal of Pharmacy and Bioallied Sciences)
Background: Sickle cell disease (SCD), thalassemia, and glucose-6-phosphate dehydrogenase (G6PD) deficiency are significant genetic disorders prevalent in Central India, particularly among tribal populations. Early detection through the neonatal screening can improve health outcomes. Aim and Objective: This study aims to assess the prevalence of SCD, thalassemia, and G6PD deficiency in a cohort of newborns from tribal regions in Central India and to evaluate the effectiveness of neonatal screening programs. Materials and Methods: A total of 382 newborns were screened using high-performance liquid chromatography (HPLC) for hemoglobinopathies and a colorimetric method for G6PD deficiency. Data on demographics and family history were collected and analyzed. Results: The screening revealed 22 cases of SCD (5.8%), 37 cases of thalassemia (9.7%), and 29 cases of G6PD deficiency (7.6%). A significant correlation was found between family history and the prevalence of these disorders. Conclusion: The findings highlight the need for comprehensive neonatal screening programs in tribal populations to enhance early detection and management of genetic disorders.